Profiling Hormonal Contraceptive Use and Perceived Impact on Training and Performance in a Global Sample of Women Rugby Players - Natalie Brown (International Journal of Sports Physiology and Performance)
Purpose: The potential impact of hormonal contraceptives (HCs) on player health and performance in women’s rugby union (rugby) is not well understood, despite rugby’s growing popularity worldwide. This study investigated the prevalence of HC use and reported associations with training and performance in a global sample of women rugby players. Method: A globally distributed online survey, seeking to explore experiences in women’s rugby, was completed by 1596 current or former adult women 7s or 15s rugby players (mean age 27 [6] y; 7 [5] y playing experience) from 62 countries. The survey included a section of questions about reported HC use, including the type, reason for use, symptoms, and experiences relating to rugby training and performance. Results: A total of 606 (38%) participants from 33 of the 62 (53%) countries reported using HCs, with the combined oral contraceptive pill reported as the most frequently used (44%). Almost half of participants using HCs (43%) tracked HC-related symptoms. Over 10% reported altered rugby performance due to HC-related symptoms, 22% required medication to manage symptoms, and 11% used HCs to control or stop their menstrual periods for rugby training and performance. Conclusions: The current study highlights the prevalence of HC use in women’s rugby, identifying practices that may negatively affect performance, health, and well-being. Thus, there is an urgent need to better understand the motivations for such practices and knowledge of potential side effects among women rugby players across all levels and countries.